The almanac of american politics 1994 - Barone, M., Ujifusa, G. (Washington D. C. National Journal, 1994)
In this writing Michael Barone has created an authoritative roadmap that shows how Americans are using the political process as a means for redefining their role in the new world order.
Keywords: Politics